Pravila merjenja in vrednotenja postavk v računovodskih izkazih po ZGD-1 - Odar, Marjan (Podjetje in delo, 2022)
In order to comply with the Accounting Directive, the provisions of Article 67 of the Companies Act setting out the rules for measuring and valuing items in financial statements have been amended. The author comments and explains the provisions of the Companies Act in the light of the provisions of the Directive, the Slovenian Accounting Standards, IAS and IFRS. In addition to the general accounting rules, the author also discusses the rules for measuring property, plant and equipment, determining fair value of financial assets, recognising profits or losses arising from changes in fair value, the rules for valuing investments in subsidiaries and associates, the division of assets into short-term and long-term ones, the rules for timing of recognition of dividend income, creating valuation allowances for fixed assets, measuring current assets, prohibiting capitalising start-up costs and reducing accumulated profit by capitalised long-term deferred development costs, the definition of provisions, and the basic rules for accounting for biological assets.
Keywords: accounting standards; Companies Act; fair value; finančna sredstva; historical cost principle; izvirna vrednost; measurement of items; merjenje postavk; poštena vrednost; računovodski standardi; revalorizacija; revaluation; valuation of items; vrednotenje postavk; Zakon o gospodarskih družbah